Internal Audit as a Guard Against Fraud Risks - Ricky Bryan D.P. Tampubolon (CV. ITTC INDONESIA, 2026)
Employee fraud represents a serious threat to organizational sustainability as it causes financial losses, damages reputation, and weakens stake-holder trust. This study aims to examine the effects of opportunity, rationalization, and pressure on employee fraud, as well as to assess the role of internal audit as a moderating variable. The research design em-ploys a quantitative approach using a survey method with 120 respondents from private companies in Jakarta. Primary data were collected through questionnaires and analyzed using multiple linear regression and interaction tests. The findings reveal that opportunity, rationalization, and pressure have a positive effect on employee fraud. However, internal audit is proven to weaken the influence of these three factors, although it does not have a direct effect on fraud. This highlights the strategic role of internal audit as a control mechanism capable of reducing opportunities, limiting rationalizations for fraudulent behavior, and mitigating the impact of pressures experienced by employees. The implications of this research emphasize the importance of strengthening the in-ternal audit function within corporate governance systems and open theoretical avenues for examining the role of internal audit as a moderator in the fraud model.